Cracking the code of speech act and translation quality in “A Space for the Unbound” - Putri, Astari Amalia (Universitas Islam Malang, 2025)
As the global gaming market grows, localizing video games has become essential to reaching international audiences. It is not just about translating words; it is also about preserving the emotions behind them. This is especially true for expressive speech acts, which convey feelings like gratitude, apology, or sorrow. While Indonesian-made games are gaining worldwide popularity, little is known about how well their delivery and translations capture the emotional depth of the original story. This study explores expressive speech acts in A Space for the Unbound, a popular Indonesian game with a growing global fan base. It also examines whether the Indonesian translation effectively conveys the emotions found in the original English text. Using a descriptive qualitative approach, the research compares English expressive speech acts from the game’s prologue and Chapter 1 to their Indonesian translations. The speech acts are categorized using a mix of expert models, and the translation is evaluated based on accuracy, readability, and acceptability. The findings reveal a high frequency of expressive speech acts, evenly distributed to elicit emotional responses in players. The translation quality is excellent, with all three dimensions exceeding 95%. Small adjustments to accuracy (around 5%) seem intended to enhance emotional engagement. This research demonstrates that a successful game translation necessitates a balance between accurate language and cultural and emotional meaning, providing practical insights for game developers and localization experts working across languages.